Penggunaan Aplikasi Multikey Sebagai Upaya Meningkatkan Kompetensi Guru Pendidikan Agama Islam dalam Menulis Huruf Hijaiyyah Berbasis Komputer: (Studi pada Kegiatan Pendampingan Guru PAI SMP Kota Cilegon Semester Genap Tahun Pelajaran 2016/2017) - Ahmad Syukri (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2018)
The digital age of a teacher is also required to adapt to the computer. PAI teachers are required to be able to use computers to help their tasks and roles as professional educators, including the ability to write computer-based Hijaiyyah letters. But apparently the problem is not that simple, because he has to adapt to a keyboard that generally uses Latin letters where there are very striking differences (even 100% different) between Latin and Arabic letters. In the mentoring activities of the PAI Middle School Teacher in the City of Cilegon, the writer introduced a practical way to write Arabic letters using the Multikey application, a product of Indonesian sons that is not yet widely known. The data collection was carried out by the writer through literature review, interviews, and direct observation of the author in the activities of mentoring PAI teachers in Cilegon City. While processing data through descriptive analysis, drawing conclusions through deductive and inductive methods. The conclusions of this paper are (1) The main problem of the PAI teacher in Cilegon City Junior High School in writing computer-based Hijaiyyah letters is the different letters on the keyboard, between Latin and Arabic, while the available keyboard is only Latin; (2) Multikey application program is a practical program of writing Hijaiyyah letters that have the characteristics of the similarity of letters between Arabic and Latin on a Latin keyboard; (3) The procedure for operating a multikey application program is very easy because it is equipped with a simple tutorial; and (4) 81.5% PAI Middle School Teachers in Cilegon City feel helped by the Multikey application program because they no longer need to memorize the position of the Hijaiyyah letters on the keyboard. The remaining 18.5% are not interested in applying multikey on their computers because of their computing capabilities, in general, do not yet support.